2004
DOI: 10.1143/jpsj.73.412
|View full text |Cite
|
Sign up to set email alerts
|

Ordered Phases and Phase Transitions in The Stacked Triangular Antiferromagnet CsCoCl3and CsCoBr3

Abstract: We study the ordered phases and the phase transitions in the stacked triangular antiferromagnetic Ising (STAFI) model with strong interplane coupling modeling CsCoCl 3 and CsCoBr 3 . We find that there exists an intermediate phase which consists of a single phase of so-called partial disordered (PD) type, and confirm the stability of this phase. The low temperature phase of this model is so-called two-sublattice ferri magnetic phase. The phase transition between the PD phase and two-sublattice ferri magnetic p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 14 publications
1
26
0
2
Order By: Relevance
“…1.13a) is realized in the finite temperature region in between the low temperature FR ordered state and the high-temperature paramagnetic phase. So far, the only PD state confirmed is in a threedimensional model with stacked triangular lattices, in which the interlayer spin-spin coupling being stronger than the intralayer couplings [54]. In a series of the subsequent studies, the phase diagram of this model was studied extensively using the classical MC simulation for both weak J 2 [11-13, 49, 57] and for J 2 being comparable to J 1 [24].…”
Section: Partially Disordered Statementioning
confidence: 99%
“…1.13a) is realized in the finite temperature region in between the low temperature FR ordered state and the high-temperature paramagnetic phase. So far, the only PD state confirmed is in a threedimensional model with stacked triangular lattices, in which the interlayer spin-spin coupling being stronger than the intralayer couplings [54]. In a series of the subsequent studies, the phase diagram of this model was studied extensively using the classical MC simulation for both weak J 2 [11-13, 49, 57] and for J 2 being comparable to J 1 [24].…”
Section: Partially Disordered Statementioning
confidence: 99%
“…The magnetic 3FR state does not appear when the lattice is not distorted. 6) Lattice and spin degrees of freedom and nonequivalence interactions induce the appearance of (3FR, 3FR) phase.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of experimental and theoretical studies have been carried out for hexagonal ABX 3 -type substances such as CsCoCl 3 and CsCoBr 3 because of the successive magnetic phase transitions due to the strong spin frustration. [1][2][3][4][5][6] These substances consist of quasione-dimensional spin chains because the intrachain antiferromagnetic exchange interaction is much stronger than the interchain antiferromagnetic exchange interaction. Substances of this type are expressed by the stacked triangular antiferromagnetic Ising model.…”
Section: Introductionmentioning
confidence: 99%
“…Although such PD state was indeed observed in several Co compounds [5,6], subsequent Monte Carlo (MC) simulations indicated that, in purely two-dimensional systems, the PD appears at most as a quasi-LRO and that the transition from the high-T paramagnetic phase is of Kosterlitz-Thouless (KT) type [7][8][9][10][11][12]. The results suggest that, for establishing a PD LRO, it is indispensable to incorporate additional elements, such as a three-dimensional interlayer coupling [13].In this Letter, we explore the possibility of PD LRO in two dimensions when taking account of the coupling to itinerant electrons. Our study is partly motivated by the recent discovery of PD in metallic compounds with quasi-two-dimensional structure [14].…”
mentioning
confidence: 96%